Amr Ma'ruf wa Nahi Munkar: Gerakan Kadizadeli dan Kritik Sufisme di Kerajaan Ottoman Abad ke-17: Amr Ma’ruf wa Nahi Munkar: Kadizadeli Movement and Critique of Sufism in the 17th Century Ottoman Empire - Fahmi Rizal Mahendra (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2022)
This research will explore the Kadizadeli movement in the Ottoman empire in the 17th century. The Kadizadeli movement is a movement led by clerics who were previously Friday preachers at mosques in Istanbul. This movement wanted to purify Islam from the heretical behavior and activities of the Sufis who according to them had demoralized Ottoman society in the 17th century. In Islamic history, for example, there are several figures who also criticized Sufism, Ibn Tayimiyah or Ibn Jauzi. The complex problems of the 17th century have inspired some scholars, especially Kadizadeli, to fix them. Using the jargon, Amr ma'ruf wa nahi munkar, they began to criticize and attack the practices of Sufism in the Ottoman empire. By using historical research and literature this research produced several findings. Historically, this movement was led by three people, namely: Kadizade Mehmed, Ustuvani Mehmed and Vani Mehmed. Initially this movement only conveyed their criticism of Sufism activities through sermons and writings. However, when Ustuvani and Vani led this movement and gained a special relationship with the ottoman rulers, this movement led to radical actions. Apart from criticizing and criticizing, they also attack the infrastructure of Sufism and direct physical attacks on them.  Keywords :  bidah, kadizadeli, ottoman empire, sufism, ulema